2014
DOI: 10.1016/j.jpeds.2014.01.051
|View full text |Cite
|
Sign up to set email alerts
|

Climbing the Branches of a Family Tree: Diagnosis of Fragile X Syndrome

Abstract: Objective To determine the average number of family members who are diagnosed with a Fragile X Mental Retardation-1 (FMR1) mutation after a proband receives the initial diagnosis of Fragile X syndrome (FXS). Study design We reviewed pedigrees of families who have been evaluated at the Fragile X Center at Emory University, Atlanta, GA. Through these pedigrees, we determined the number of additional family members diagnosed as FMR1 premutation carriers or with full mutation FXS, following the initial diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…From 106 initial probands with FXS, there was a threefold discovery of family members with either a premutation or full mutation. This result is similar to a previous study which revealed that after the initial diagnosis of a proband with FXS, on average at least five additional family members were diagnosed with an FMR1 mutation [Visootsak et al, ]. The standard practice of taking a genetic pedigree resulted in cascade screening, an active process to find immediate and extended family members affected with inherited genetic conditions, for which interventions may exist to aid individuals after the case‐finding.…”
Section: Discussionsupporting
confidence: 89%
“…From 106 initial probands with FXS, there was a threefold discovery of family members with either a premutation or full mutation. This result is similar to a previous study which revealed that after the initial diagnosis of a proband with FXS, on average at least five additional family members were diagnosed with an FMR1 mutation [Visootsak et al, ]. The standard practice of taking a genetic pedigree resulted in cascade screening, an active process to find immediate and extended family members affected with inherited genetic conditions, for which interventions may exist to aid individuals after the case‐finding.…”
Section: Discussionsupporting
confidence: 89%
“…For example, the parents of a newly diagnosed child may need to consider the possible impact of an FMR1 expansion on not only the child and carrier parent, but also the possibility of a grandparent developing FXTAS, as well as the reproductive impact for siblings, aunts, or cousins. 109 Future reproductive decisions will also be impacted. In qualitative interview studies of reproductive decisions made by carrier mothers, 110,111 the majority (77%) had decided not to have more biological children because of the 50% risk of passing on the mutation to their child.…”
Section: Resultsmentioning
confidence: 99%
“…109 Pediatricians can help increase awareness of and support families in receiving services, such as referrals for genetic testing and counseling, behavioral therapies, psychological counseling, psychopharmacology, and educational interventions. This support includes services for a clinically referred child, as well as other affected family members.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, pediatricians may be called on to support the larger family system, because a diagnosis of 1 individual can impact many other family members. 204 These basics are reviewed in this article, although if the pediatrician feels uncomfortable regarding these points, they can refer to a specialist, such as a developmental-behavioral pediatrician or psychiatrist, for psychopharmacologic intervention or a genetic counselor to discuss extended family involvement and reproductive options.…”
Section: Discussionmentioning
confidence: 99%